2021
DOI: 10.3329/dshj.v36i2.54386
|View full text |Cite
|
Sign up to set email alerts
|

A Study On Clinical and Laboratory Profile of Children with COVID-19 Attending A Tertiary Care Hospital in Bangladesh

Abstract: Background: An outbreak of COVID-19 caused by 2019 novel coronavirus started first in Wuhan, Hubei province of China. Thereafter it spreaded to different countries of the world. Cases among children has been increasing day by day. Despite taking all measures of prevention virus spreading is uncontrolled. Objectives: To determine the clinical features and laboratory profile of children with COVID-19. Methods: This was a cross sectional study conducted in Dr. MR Khan Shishu Hospital and Institute of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…3 Iman K et al 6 conducted a study at Dr. MR Khan Shishu Hospital and Institute of Child Health, Dhaka & Ghosh UK et al 7 also conducted a crosssectional study in same hospital from April 2020 to August 2020 on COVID-19 cases (shown in Table-I). Fever, cough, diarrhea & anorexia was found as common symptoms 6,7 Rahman M et al 9 found a good number of cases of COVID-19 infection in neonate. Out of 1714 admitted neonates in Dhaka Shishu (Children) Hospital, 32(2%) cases were found COVID-19 infection.…”
Section: Impact Of Covid-19 On Child Life and Health In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Iman K et al 6 conducted a study at Dr. MR Khan Shishu Hospital and Institute of Child Health, Dhaka & Ghosh UK et al 7 also conducted a crosssectional study in same hospital from April 2020 to August 2020 on COVID-19 cases (shown in Table-I). Fever, cough, diarrhea & anorexia was found as common symptoms 6,7 Rahman M et al 9 found a good number of cases of COVID-19 infection in neonate. Out of 1714 admitted neonates in Dhaka Shishu (Children) Hospital, 32(2%) cases were found COVID-19 infection.…”
Section: Impact Of Covid-19 On Child Life and Health In Bangladeshmentioning
confidence: 99%
“…Jamal CY et al 14 commented regarding higher paediatric fatalities relating to COVID-19 and concluded that malnutrition and high prevalence of vitamin D deficiency among Bangladeshi children may be contributing factors of higher infection rates and mortality. 3,6,7 among Bangladeshi children (Data were shown in percentile)…”
Section: Impact Of Covid-19 On Child Life and Health In Bangladeshmentioning
confidence: 99%